Prognostic significance of CCND1 (cyclin D1) overexpression in primary resected non-small-cell lung cancer. - Betticher, D. C. (Nature Publishing Group, 1996)
Amplification of the CCDN1 gene encoding cyclin D1 was examined by Southern blotting and multiplex polymerase chain reaction (PCR) and occurred in 8 of 53 patients (15%) with primary resected non-small-cell lung cancer (NSCLC). These tumours and 17 additional tumours with a normal gene copy number showed overexpression of cyclin D1 (25/53, 47%), as assessed by immunostaining using a monoclonal antibody. In 22/25 cases, cyclin D1 was localised in the cytoplasm, but some (7/25) had simultaneous nuclear staining. This result is in marked contrast to that reported in breast, hepatocellular and colorectal carcinoma studies where immunostaining was invariably nuclear. Examination of a restriction fragment length polymorphic (RFLP) site within the 3'untranslated region of the cDNA following reverse transcriptase (RT)-PCR (29/53 informative cases) showed a strong association between cytoplasmic staining and imbalance in allele-specific message levels. Cyclin D1 overexpression was associated with a poorly differentiated histology (P = 0.04), less lymphocytic infiltration of the tumour (P = 0.02) and a reduction in local relapse rate (P = 0.01). The relative risk of local relapse was 9.1 in tumours without cyclin D1 overexpression (P = 0.01, Cox regression analysis). We conclude that genetic alteration of cyclin D1 is a key abnormality in lung carcinogenesis and may have diagnostic and prognostic importance in the treatment of resectable NSCLC. IMAGES: